Hak Restitusi bagi Korban Perdagangan Orang: Sebuah Langkah Penting Menuju Keadilan di Indonesia - Khairul Riza (Kajian Ilmiah Hukum dan Kenegaraan, 2023)
Purpose: The purpose of this study was to determine the implementation of restitution rights for trafficking victims in Indonesia, the obstacles and challenges faced in the process of providing restitution for trafficking victims in Indonesia, and how it impacts the victim recovery process. Methodology: The method used is Empirical juridical research was conducted through a series of field interviews with respondents and informants. It also uses normative research, namely research through literature studies. Result: The results showed that in the context of granting restitution rights to trafficking victims in Indonesia, despite the supporting legal foundation, implementation on the ground has not fully reflected the values of justice espoused in Pancasila, especially in the precepts of "Just and Civilized Humanity". The provision of restitution is not only a matter of compensation but also a form of state recognition of the dignity and humanity of each victim. Thus, restitution must be carried out with a sense of justice, without discrimination, to ensure full recovery for victims. The recovery process for trafficking victims in Indonesia faces various challenges, particularly those related to obstacles to the provision of restitution. Such barriers not only impact the financial aspects of victims but also their psychological, physical, and social recovery into society. The success of restitution is an important indicator of a country's commitment to ensuring justice and redress for the victims of exploitation.